Pengaruh Motivasi Belajar dan Lingkungan Teman Sebaya Terhadap Hasil Belajar Ekonomi Siswa Jurusan IIS di SMA Laboratorium Undiksha - Surbakti, Difia Febrina; Dharmayasa, I Putu Arya (Jurnal Pendidikan Ekonomi Undiksha, 2024)
This study aims to determine the effect of learning motivation variables and peer environments on student learning outcomes majoring in IIS at Undiksha Laboratory High School. The population in this study were grade XI and grade XII students majoring in IIS at Undiksha Laboratory High School. In this study, the sample to be taken is all students majoring in IIS at Undiksha Laboratory High School, totaling 42 students. The sampling technique in this study was saturated sampling technique. The data in the study were collected by distributing questionnaires. The analysis technique used is multiple linear regression analysis with partial (t test) and simultaneous (F test) hypothesis testing. The results of this study indicate that (1) there is an influence of learning motivation on learning outcomes, (2) there is an influence of peer environment on learning outcomes, and (3) there is a simultaneous influence of learning motivation and peer environment on the economic learning outcomes of students majoring in IIS at Undiksha Laboratory High School.